EP968 Practice trend of PLD in ovarian cancers: experience from tertiary cancer centre in india. (1st November 2019) - Roy, R; De, S
Abstract : Introduction/Background: Pegylated liposomal doxorubicin (PLD) remains an active agent in treating epithelial ovarian cancer (EOC). It is mainly preferred in second line after progression on taxanes and platinum. Incidence of alopecia being low, PLD is often preferred over taxanes. This retrospective study looks at the practice trend of PLD in EOC. Methodology: Retrospective data was collected from 52 patients suffering from advanced epithelial ovarian cancer with a median age of 51 years were administered Pegylated Liposomal Doxorubicin (PLD). All these patients had either undergone a primary debulking surgery or an interval cytoreduction. Results: 32 (62%) patients received PLD and Carboplatin at an interval of 4 weeks while 20 (38%) patients received PLD as monotherapy (as platinum was considered refractory in these patients). 24(46%) patients received PLD in 2nd line (16 with platinum and 8 as monotherapy) and 24 (46%) patients in 3rd line (these patients got rechallenge of Paclitaxel and Carboplatin once disease recurred beyond 6 months in 2nd line). The main reason for choosing PLD in second line was lack of response from Taxane/platinum rather than toxicity profile of PLD. 4 patients preferred PLD in second line because of lesser alopecia. Average no of cycles of PLD administered were 5 and response rates were 30%. Earlier the introduction of PLD, better was the response. Adverse events noted with PLD were neutropenia 5(10%) patients, alopecia 4(8%) patients, PPE 3(6%) patients. Cardiotoxicity was not detected. There were no treatment discontinuations in the PLD only group. In the PLD and Carboplatin group 2 patients had platinum hypersensitivity, thereby leading to omission of platinum. Conclusion: Tolerance to PLD amongst patients were high, however paclitaxel and carboplatin still remains as one of the priority regimens in second line if disease recurs >6 months in this part of world. Disclosure: Nothing to disclose.